Type revision of Asiatic bees of the genus Hylaeus F. described by Ferdinand Morawitz (Hymenoptera: Apoidea, Colletidae) - Dathe, Holger H.; Proshchalykin, Maxim Yu. (Zootaxa, 2017)
The type specimens of the bee genus Hylaeus Fabricius, 1793 described by Ferdinand Morawitz from Asia and deposited in the Zoological Museum of the Moscow State University and in the Zoological Institute, Russian Academy of Sciences St. Petersburg, are critically reviewed. Precise information with illustrations of types for 39 taxa is provided. New synonymy is established for Hylaeus incongruus Förster, 1871 (= H. biareolatus Morawitz, 1876, syn. nov.); H. breviceps Morawitz, 1876 (= H. bivittatus Morawitz, 1876, syn. nov.); H. punctiscapus Morawitz, 1876 (= H. citrinipes Morawitz, 1893, syn. nov.); H. dolichocephalus Morawitz, 1876 (=Prosopis heliaca Warncke, 1992, syn. nov.); H. laticeps Morawitz, 1876 (= H. nigritarsis Morawitz, 1876, syn. nov.); H. medialis Morawitz, 1890 (= H. bimaculatus Chen & Xu, 2013, syn. nov.). Lectotypes are here designated for the following six nominal taxa: Hylaeus citrinipes Morawitz, 1893, H. flavipes Morawitz, 1876, H. ibex Morawitz, 1877, H. punctiventris Morawitz, 1876, H. trisignatus Morawitz, 1876, and H. turanicus Morawitz, 1876.